Utilizando títulos de artigos científicos na construção de redes semânticas para caracterizar áreas de pesquisa - Souza, Jansen Cruz de (2015)
The scientific knowledge is not just the discovery of new facts and laws, but also in its publication. Aiming to understand the complex scientific production system analysis techniques have been applied in many digital repositories. Therefore, the social network analysis (SNA) has been a topic of interest of several studies in recent years. Social networks can be established from the relationship between people or the relationship of information that can be analyzed to assist decision making. The purpose of this thesis is to present a technique that makes it possible to characterize areas of scientific research by building semantic networks vary in time. These networks are built building on the co-occurrence of keywords in the titles of scientific papers, used to represent the evolution of research themes addressed by means of publication over time.